Theoretical Training of Modern School Teacher in Poland and Ukraine - Kuchai, Oleksandr (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article presents the humanization and democratization of the educational process of vocational and educational training teachers Ukraine, implementation of new educational technologies, finding the most optimal conceptual approaches to the development of national pedagogy cause growth of scientific and practical interest to study the experience of secondary and higher education, including the Republic of Poland. European requirements for teacher training, the quality of their professional qualifications and competencies, professional development of teachers - is the most pressing issue of training teachers in Europe. Polish scientists actively working on finding optimal ways of improving training of primary school teachers in higher education. The most important industrial and educational and developmental functions performed by primary school teacher in the Ukraine, is a professional and personal self-help that improve the professional competence and pedagogical skills through personal and professional selfdevelopment, creating conditions for self-development and self-disclosure by the child selfdevelopment technologies and techniques.